Analysing collision detection in a virtual environment for haptic applications in surgery (2011)
This paper presents an analysis of two commercially-available haptic interfaces that can be used in surgical training and medical simulation. Integrating development kits with open source software libraries like OpenGL and VCollide led to proposing a solution to problems like loss of tactile ability and detecting collisions between objects in a virtual environment. Haptic applications were based on results regarding capturing, processing and analysing images for building models for interaction with rigid bodies of medical interest. The application included tools for marking points and paths on a virtual surfaces and force reflection algorithms for simulating interactions with surface/volumetric 3D models. Immersion characteristics and the effect of virtual surgical instruments were analysed.